Left Atrial Appendage Closure Yields Favorable Cardio- and Cerebrovascular Outcomes in Patients With Non-valvular Atrial Fibrillation and Prior Stroke - Zhao, Mingzhong; Zhao, Mengxi; Hou, Cody R.; Post, Felix; Herold, Nora; Walsleben, Jens; Meng, Zhaohui; Yu, Jiangtao (Frontiers in Neurology, 2022)
Introduction: Patients with non-valvular atrial fibrillation (NVAF) and previous stroke are at significantly higher risk of stroke recurrence. Data on the efficacy of left atrial appendage closure (LAAC) on these patients is limited. The aim of this study was to investigate the differences of LAAC efficacy on long-term cardio- and cerebrovascular outcomes in NVAF patients with versus without prior stroke. Methods: Three hundred and seventy consecutive NVAF patients who underwent LAAC were enrolled and divided into stroke and non-stroke groups based on history of previous stroke. Endpoints, such as thromboembolism, major bleeding, and mortality post-LAAC, were followed up among groups. Results: Patients in the stroke group had higher mean CHA2DS2-VASc and HAS-BLED scores compared to the non-stroke group (5.1 vs. 3.6 and 4.1 vs. 3.4, both P < 0.001, respectively). Over a median follow-up of 2.2 years, there were no significant differences in incidence rates of thromboembolism, device-related thrombus (DRT), major bleeding, and combined efficacy endpoints between the two groups. In both stroke and non-stroke groups, LAAC decreased the risk of thromboembolism [relative risk reduction (RRR) 87.5%, P = 0.034, and 74.6%, P = 0.004, respectively] and major bleeding (RRR 68.8%, P = 0.034, and 68.6%, P = 0.007, respectively) compared with predicted risk. The RRR in thromboembolism was greater in patients with versus without prior stroke (OR 2.45, 95% CI: 1.20 — 5.12, P = 0.016). The incidence rates of all-cause mortality and non-cardiovascular death were similar between the two groups, but the risks of cardiovascular death post-LAAC both before (1.4% vs. 8.1%, respectively, P = 0.038) and after adjustment for confounding factors (P = 0.048) were significantly decreased in the stroke group. Conclusions: Patients with versus without prior stroke did not exhibit a worse clinical prognosis after LAAC. LAAC may provide an increased benefit in cardio-cerebrovascular outcomes in patients with previous stroke compared to those without previous stroke. Further research is necessary to evaluate the efficacy of LAAC in this field.